Guide :

# combine the like terms

8xsquare+6xto the third power +2x+5x=

## Research, Knowledge and Information :

### Combining Like Terms Lessons | Wyzant Resources

Combining Like Terms is a process used to simplify an expression or an equation using addition and subtraction of the coefficients of terms.

### Combining Like Terms - Math Is Fun

"Like terms" are terms whose variables (and their exponents such as the 2 in x 2) are the same. In other words, terms that are "like" each other. Note: the ...

### How to Combine Like Terms - Mathwarehouse.com

"Like Terms" means that you can add or subtract two terms. For instance, you know that you can add 2 +3 and get 5. You were able to add these two 'terms' ( the '2 ...

### Combining Like Terms - Free Math Help

Simplify an expression by combining like terms. In this process you will find terms that share the same variable and combine them together to form a simpler expression.

### Combining like terms (video) | Khan Academy

Let's say that you started off with 3 apples. And then I were to give you another 7, another 7 apples. So my question to you-- and this might be very obvious-- is how ...

### Polynomials: Combining "Like Terms" - Purplemath

Defines 'like terms' and demonstrates how to combine like terms. Warns against common student mistakes.

### Simplifying Expressions Calculator | Wyzant Resources

Simplifying Expressions Calculator. ... the calculator will simplify the expression by expanding multiplication and combining like terms.

### Combining like terms with negative coefficients (practice ...

Simplify algebraic expressions by combining like terms. Coefficients on some terms are negative.

### Combining Like Terms

©4 k2H0o1 w2T MKfu it Xa7 nSEowfkt EwIa OrSeA 3L KLuC v.b r 8A7lUle 3r aiSgUhTtQs n Lrse UsWeXrYvxe Bd9. F D EM Yagdqem 9w qi Nt5hy sIUnwfpidnni ut Neh ...

### Simplfy an Algebraic Expression by Recognizing Like Terms ...

Simplfy an Algebraic Expression by Recognizing Like Terms ... This page will show you how to identify and combine like terms. Type your problem here Quick!

## Suggested Questions And Answer :

### (13-3)x5=50

Simplifying x + 2 = 3x + -1x2 + 5 Reorder the terms: 2 + x = 3x + -1x2 + 5 Reorder the terms: 2 + x = 5 + 3x + -1x2 Solving 2 + x = 5 + 3x + -1x2 Solving for variable 'x'. Reorder the terms: 2 + -5 + x + -3x + x2 = 5 + 3x + -1x2 + -5 + -3x + x2 Combine like terms: 2 + -5 = -3 -3 + x + -3x + x2 = 5 + 3x + -1x2 + -5 + -3x + x2 Combine like terms: x + -3x = -2x -3 + -2x + x2 = 5 + 3x + -1x2 + -5 + -3x + x2 Reorder the terms: -3 + -2x + x2 = 5 + -5 + 3x + -3x + -1x2 + x2 Combine like terms: 5 + -5 = 0 -3 + -2x + x2 = 0 + 3x + -3x + -1x2 + x2 -3 + -2x + x2 = 3x + -3x + -1x2 + x2 Combine like terms: 3x + -3x = 0 -3 + -2x + x2 = 0 + -1x2 + x2 -3 + -2x + x2 = -1x2 + x2 Combine like terms: -1x2 + x2 = 0 -3 + -2x + x2 = 0 Factor a trinomial. (-1 + -1x)(3 + -1x) = 0 Subproblem 1 Set the factor '(-1 + -1x)' equal to zero and attempt to solve: Simplifying -1 + -1x = 0 Solving -1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 0 + 1 -1x = 0 + 1 Combine like terms: 0 + 1 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1 Subproblem 2 Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3 Solution x = {-1, 3}

### (8x)[(2x)^-2=8

Simplifying 8x = 2x2 + 8 Reorder the terms: 8x = 8 + 2x2 Solving 8x = 8 + 2x2 Solving for variable 'x'. Reorder the terms: -8 + 8x + -2x2 = 8 + 2x2 + -8 + -2x2 Reorder the terms: -8 + 8x + -2x2 = 8 + -8 + 2x2 + -2x2 Combine like terms: 8 + -8 = 0 -8 + 8x + -2x2 = 0 + 2x2 + -2x2 -8 + 8x + -2x2 = 2x2 + -2x2 Combine like terms: 2x2 + -2x2 = 0 -8 + 8x + -2x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-4 + 4x + -1x2) = 0 Factor a trinomial. 2((-2 + x)(2 + -1x)) = 0 Ignore the factor 2. Subproblem 1 Set the factor '(-2 + x)' equal to zero and attempt to solve: Simplifying -2 + x = 0 Solving -2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + x = 0 + 2 x = 0 + 2 Combine like terms: 0 + 2 = 2 x = 2 Simplifying x = 2 Subproblem 2 Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2 Solution x = {2, 2}

### Guys can you help me solve these following equations

This should help: Simplifying 3p + -1 = 5(p + -1) + -2(7 + -2p) Reorder the terms: -1 + 3p = 5(p + -1) + -2(7 + -2p) Reorder the terms: -1 + 3p = 5(-1 + p) + -2(7 + -2p) -1 + 3p = (-1 * 5 + p * 5) + -2(7 + -2p) -1 + 3p = (-5 + 5p) + -2(7 + -2p) -1 + 3p = -5 + 5p + (7 * -2 + -2p * -2) -1 + 3p = -5 + 5p + (-14 + 4p) Reorder the terms: -1 + 3p = -5 + -14 + 5p + 4p Combine like terms: -5 + -14 = -19 -1 + 3p = -19 + 5p + 4p Combine like terms: 5p + 4p = 9p -1 + 3p = -19 + 9p Solving -1 + 3p = -19 + 9p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-9p' to each side of the equation. -1 + 3p + -9p = -19 + 9p + -9p Combine like terms: 3p + -9p = -6p -1 + -6p = -19 + 9p + -9p Combine like terms: 9p + -9p = 0 -1 + -6p = -19 + 0 -1 + -6p = -19 Add '1' to each side of the equation. -1 + 1 + -6p = -19 + 1 Combine like terms: -1 + 1 = 0 0 + -6p = -19 + 1 -6p = -19 + 1 Combine like terms: -19 + 1 = -18 -6p = -18 Divide each side by '-6'. p = 3 Simplifying p = 3

### 1/4x^5-3+1/2x^5-6x-35 how do you combine like terms with this problem

Combining like terms means adding or subtracting the coefficients of terms that have the same variables. x^2 can only be combined with x^2, x^4 with x^4, and so on. In your problem, you have two terms that have an x^5 and two terms that have no variable, so you would combine the two x^5 terms and then you would combine the two non x terms. An example: 7x^2 + 3 - 4x^2 + 5x + 2 7x^2 and -4x^2 are like terms. 3 and 2 are like terms. 5x has no like terms so it just stays the same.  7x^2 - 4x^2 = 3x^2  and 3 + 2 = 5   and 5x = 5x So the answer would be    3x^2 + 5x + 5

### Whats 3x-2 over 9 equals 25 over 3x-2?

I will give you an example for this question. This might be able to help you. Simplifying 3x2 + 25x = 18 Reorder the terms: 25x + 3x2 = 18 Solving 25x + 3x2 = 18 Solving for variable 'x'. Reorder the terms: -18 + 25x + 3x2 = 18 + -18 Combine like terms: 18 + -18 = 0 -18 + 25x + 3x2 = 0 Factor a trinomial. (-9 + -1x)(2 + -3x) = 0 Subproblem 1 Set the factor '(-9 + -1x)' equal to zero and attempt to solve: Simplifying -9 + -1x = 0 Solving -9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -1x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -1x = 0 + 9 -1x = 0 + 9 Combine like terms: 0 + 9 = 9 -1x = 9 Divide each side by '-1'. x = -9 Simplifying x = -9 Subproblem 2 Set the factor '(2 + -3x)' equal to zero and attempt to solve: Simplifying 2 + -3x = 0 Solving 2 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = 0 + -2 -3x = 0 + -2 Combine like terms: 0 + -2 = -2 -3x = -2 Divide each side by '-3'. x = 0.6666666667 Simplifying x = 0.6666666667 Solution x = {-9, 0.6666666667}

### how do you combine like terms with the same variable?

Like terms are where the exponents and the variable are the same but the coefficients may be different. Constants are all considered to be like terms. The same variable with different exponents can only be combined by factorisation, the variable with the lowest exponent usually being a common factor. Factorisation can also be used when two coefficients have a common factor. You can't combine different variables, even if they have the same exponent. Factorisation can be used when you have products of different variables. EXAMPLE 16+3x^3+5x^2+2x^3-y^2-x+4y+8x+y+6y^2-2x+9-25 can be simplified: x^3 term: 3x^3+2x^3 is 5x^3 x^2 term: 5x^2 only y^2 term: -y^2+6y^2 is 5y^2 x term: -x+8x-2x is 5x y term: 4y+y is 5y constant: 16+9-25 is 0 So we have: 5x^3+5x^2+5y^2+5x+5y. But 5 is a common factor: 5(x^3+x^2+y^2+x+y). Further factorisation is possible but looks clumsy: 5(x(x^2+x+1)+y(y+1))

### how to solve for x with fractions

Simplifying x3 + 3x2 + -4x = 0 Reorder the terms: -4x + 3x2 + x3 = 0 Solving -4x + 3x2 + x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-4 + 3x + x2) = 0 Factor a trinomial. x((-4 + -1x)(1 + -1x)) = 0 Subproblem 1 Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0 Subproblem 2 Set the factor '(-4 + -1x)' equal to zero and attempt to solve: Simplifying -4 + -1x = 0 Solving -4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 0 + 4 -1x = 0 + 4 Combine like terms: 0 + 4 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4 Subproblem 3 Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1 Solution x = {0, -4, 1}

### Solve 6-(5r)=5r-3, 12p-7=3p+8, 10(-4+y)=2y, -(8n-2)=3+10(1-3n), and 1/4(60+165)=15+45

1). 6 - (5r) = 5r - 3     6 -5r = 5r - 3 (distribute the negative)        -5r = 5r - 3 - 6 (subtract 6 from both sides)      -10r = -9 (subract 5r from both sides and combine like terms)           r = -9/-10 (divide by -10 on both sides)           r = 9/10 (negative divided by negative = positive) 2). 12p - 7 = 3p + 8            12p = 3p + 8 + 7 (add 7 to both sides)     12p - 3p = 15 (subtract 3p from both sides and add like terms)              9p = 15 (combine like terms on left)                p = 15/9 (divide both sides by 9) 3). 10 (-4 + y) = 2y        -40 + 10y = 2y (distribute the 10)                  10y = 2y + 40 (add 40 to both sides)           10y - 2y = 40 (subtract 2y from both sides)                    8y = 40 (combine like terms)                      y = 5 (divide both sides by 8) 4). -(8n - 2) = 3 + 10(1 - 3n)        -8n + 2 = 3 + 10 - 30n  (distribute)              -8n = 3 + 10 - 30n - 2 (subtract 2 from both sides)    -8n + 30n = 3 + 10 - 2 (add 30n to both sides)              22n = 11 (combine like terms)                  n = 11/22 (divide each side by 22)                  n = 1/2 (simplify) 5).        1/4(60 + 165) = 15 + 45      1/4(60) + 1/4(165) = 15 + 45 (distribute 1/4 to numbers inside ())               60/4 + 165/4 = 60 (combine numbers on right)                           225/4 = 60 (add fractions together)                                  0 = 60(4/4) - 225/4 (subtract 225/4)                                  0 = 240/4 - 225/4 (find common denominator)                                  0 does not equal 15/4 (subtract)                                  impossible. (impossible to solve)

### How do you solve (18x+1) + (4x-2x) = 140

Simplifying 2x + 140 = 4x + 16 Reorder the terms: 140 + 2x = 4x + 16 Reorder the terms: 140 + 2x = 16 + 4x Solving 140 + 2x = 16 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 140 + 2x + -4x = 16 + 4x + -4x Combine like terms: 2x + -4x = -2x 140 + -2x = 16 + 4x + -4x Combine like terms: 4x + -4x = 0 140 + -2x = 16 + 0 140 + -2x = 16 Add '-140' to each side of the equation. 140 + -140 + -2x = 16 + -140 Combine like terms: 140 + -140 = 0 0 + -2x = 16 + -140 -2x = 16 + -140 Combine like terms: 16 + -140 = -124 -2x = -124 Divide each side by '-2'. x = 62 Simplifying x = 62